The H3 histone chaperone NASPSIM3 escorts CenH3 in Arabidopsis. (14th October 2019) - Le Goff, Samuel; Keçeli, Burcu Nur; Jeřábková, Hana; Heckmann, Stefan; Rutten, Twan; Cotterell, Sylviane; Schubert, Veit; Roitinger, Elisabeth; Mechtler, Karl; Franklin, F. Christopher H.; Tatout, Christophe; Houben, Andreas; et al.
Summary: Centromeres define the chromosomal position where kinetochores form to link the chromosome to microtubules during mitosis and meiosis. Centromere identity is determined by incorporation of a specific histone H3 variant termed CenH3. As for other histones, escort and deposition of CenH3 must be ensured by histone chaperones, which handle the non‐nucleosomal CenH3 pool and replenish CenH3 chromatin in dividing cells. Here, we show that the Arabidopsis orthologue of the mammalian NUCLEAR AUTOANTIGENIC SPERM PROTEIN (NASP) and Schizosaccharomyces pombe histone chaperone Sim3 is a soluble nuclear protein that binds the histone variant CenH3 and affects its abundance at the centromeres. NASP SIM3 is co‐expressed with Arabidopsis CenH3 in dividing cells and binds directly to both the N‐terminal tail and the histone fold domain of non‐nucleosomal CenH3. Reduced NASP SIM3 expression negatively affects CenH3 deposition, identifying NASP SIM3 as a CenH3 histone chaperone. Significance Statement: Histone chaperones ensure escort and supply of histone proteins and may promote their assembly into nucleosomes. Here we show that the conserved histone chaperone NASP SIM3 escorts the centromere‐specific CenH3 histone variant in Arabidopsis.